Self-aligned concentrating immersion-lens arrays for patterning and efficiency recovery in scaffold-reinforced perovskite solar cells. (September 2020) - Printz, Adam D.; Zhao, Oliver; Hamann, Stephen; Rolston, Nicholas; Solgaard, Olav; Dauskardt, Reinhold H.
Highlights: Scaffold-reinforced perovskite solar cells were mechanically robust, but suffered from current losses. Self-aligned lens arrays utilized to fabricate perovskite-reinforcing scaffolds by maskless photolithography. Lens arrays successfully recovered approximately 90% of lost photocurrent in scaffold-reinforced perovskite solar cells. Lens arrays were found to be UV stable for at least 1000 h. Abstract: Unlike existing silicon, CIGS, and multi-junction cells that exhibit remarkable mechanical durability, perovskite solar cells have been shown to delaminate when subjected to the mechanical loads that occur during processing and field exposures, limiting their potential as a reliable solar technology. Mechanical reinforcement is thus essential for durable and reliable perovskite technologies. A recent strategy to overcome the thermomechanical fragility of perovskite solar cells is to extrinsically shield them by introducing reinforcing scaffolds which partition the cell into many distinct microcells, but improvements in mechanical stability coincide with a reduced device efficiency due to parasitic absorption by the scaffold. We address this reduced efficiency by integrating concentrating immersion-lens arrays (CILAs) into scaffold-reinforced solar cells. These scaffolds are lithographically patterned by a maskless process, in which ultraviolet light is used to pattern the scaffolds through the CILAs, ensuring self-alignment and optical contact with the microcells. This process creates mm-scale scaffold patterns with a line edge roughness of 17.5 ± 4.3 µm and line width roughness of 26.4 ± 8.5 µm. Perovskite devices are deposited into the microcells, and during operation, light is concentrated into the microcells and away from the insulating scaffolds, resulting in mechanically resilient solar cells with efficiencies comparable to planar devices. The devices with the strongest lenses—i.e., lower radius of curvature—recover up to 89 ± 15% of photocurrent and 91 ± 29% power conversion efficiency that would have been otherwise lost to parasitic absorption. Ray-tracing simulations of the CILAs also demonstrate passive tracking of incident light which is critical for optimal power output as the sun moves across the sky during the day. In these simulations, devices with CILAs showed improved passive tracking compared to devices without CILAs out to 60° off-normal. The UV stability of CILAs are experimentally verified through aging tests which show no change in their mechanical integrity after 1000 h of UV exposure. The simplicity of the fabrication process and the efficiency of the resulting scaffolded devices show that a lens-integrated scaffold-reinforced structure is a potential pathway to high-performance, robust, commercially viable perovskite solar cells.